Internalisasi Pendidikan Karakter Perspektif Pesantren - Zaini Dahlan (STAIFAS-Press, 2016)
Character is a basic value that can build up a person's personality, it is formed either due to the influence of heredity and environmental influences, which distinguishes it from others, and embodied in the attitudes and behavior in everyday life. Someone who can be said to be of good character or excel are those who are always trying to do things the best against Almighty God, ourselves, our fellow human beings, the environment and even the nation and the State. Character values that can be identified there are no core values (core values) value for the personal character (honest and intelligent) and social value for the character (respite and care) .Pesantren in the implementation of character education is not only a theoretical but also practical directly, Education characters like this are important, because something esensialtetap trying to stand on the ability of self (self-reliance), confident, and prioritize simplicity and firmness.Key Word: Internalization, Character, Pesantren